Panik før, under og efter en nedlukningstid: børns mediebrug under coronakrisen - Lundtofte, Thomas; Johansen, Stine Liv (Aktualitet - Litteratur, kultur og medier, 2021)
The media practices of children and youth have often been subject to polarized debates in which ‘media’ are portrayed as harmful and something which must be contained. Kirsten Drotner’s canonized concept of media panics speaks to this issue and the concept itself has also been the subject of discussions elsewhere. This article reflects on the role of media in children’s everyday lives in light of the ongoing crisis due to Covid-19. The article presents empirical examples from the research project “Children’s Digital Lives during Covid-19” as well as international perspectives, and through these it relates to the ongoing societal focus on digital literacy and children’s media practices.